AKLIMATISASI TANAMAN ANTHURIUM (Athurium Sp) DENGAN BERBAGAI MEDIA TUMBUH DAN PUPUK DAUN GROWQUICK - Julhendri Julhendri; Hercules Gultom; Fathurrahman Fathurrahman (UIR Press, 2013)
The purpose of the research was to recognize the effect of interaction various planting media and growquick fertilizer on Anthurium growth resulting from tissue culture. This research was conducted at the green house of Faculty Agriculture Riau Islamic University during three months, from January to March 2011. The completely randomized design with two factors was used. The factor M (media) consisted of 4 treatments and G (Growquick) consisted of 4 treatments and three replications. The M factor namely M0 (without media), M1 (burned husk and coco peat; 1:1), M2 (burned husk and cut edible fern; 1:1), and M3 (cut edible fern and coco peat; 1:1). The G factor, i.e, G0 (witout media), G1 (growquick fertilizer 2.5 ml/lt water), G2 ((growquick fertilizer 5 ml/lt water), and G3 ((growquick fertilizer 7.5 ml/lt water). The observed parameters were plant height, number of leaf per plant, wide leaf, length of the longest leaf, root number, and length of the longest root. The result showed that interactionally application of various growth media of cut edible fern + coco peat and growquick 5.0 ml/lt water on authorium affected on number of leave per plant and length of leaf. The treatment of various growth media only affected on all parameters observed with the best treatment M3. The treatment of growquick fertilizer only affected on all parameters observed with the best treatment of G2 (5.0 ml/lt water).